Syrian Foreign Trade And Its Impact On Economic Growth During The Period 2000-2017 (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2019)
Foreign trade is one of the main sectors contributing to the national economy. The research is concerned with studying the relationship between the growth and development of foreign trade and the economic growth represented by GDP. This relationship is widely debated among economists, although some research has found a positive relationship between them. A negative relationship. It was noted in this research through the study of the evolution of the Syrian trade balance in the period 2000-2017 that the trade balance suffers from a continuous deficit during the study period in general and has worsened significantly during the war years, and the low rate of export coverage of imports, where the research showed an inherent structural defect In the foreign trade sector, especially in the commodity structure of exports and imports according to their use (consumer, intermediary, capitalist). The study found a long-term equilibrium relationship between the total foreign trade and GDP in the Syrian Arab Republic during the study period and based on the Granger causality test, it shows a unidirectional causal relationship between total foreign trade and GDP. تعتبر التجارة الخارجية من القطاعات الأساسية المساهمة في الاقتصاد الوطني، ويهتم البحث بدراسة العلاقة بين نمو وتطور التجارة الخارجية والنمو الاقتصادي الممثل بالناتج المحلي الإجمالي حيث تحظى هذه العلاقة بجدل واسع بين الاقتصاديين رغم أن بعض الأبحاث توصلت إلى وجود علاقة ايجابية بينهما، بينما توصلت أبحاث أخرى إلى وجود علاقة سلبية. لوحظ في هذا البحث من خلال دراسة تطور الميزان التجاري السوري في الفترة 2000-2017 أن الميزان التجاري يعاني من عجز مستمر خلال فترة الدراسة بشكل عام وقد تفاقم العجز بشكل كبير خلال سنوات الحرب، وانخفاض نسبة تغطية الصادرات للواردات، حيث أظهر البحث وجود خلل بنيوي المتأصل في قطاع التجارة الخارجية وخاصة في التركيب السلعي للصادرات والواردات بحسب استخدامها (استهلاكي، وسيط، رأسمالي). وقد توصلت الدراسة إلى وجود علاقة توازنية طويلة الأمد بين إجمالي التجارة الخارجية والناتج المحلي الإجمالي في الجمهورية العربية السورية خلال فترة الدراسة و بالاعتماد على اختبار السببية ل Granger، تبيين وجود علاقة سببية أحادية الاتجاه بين إجمالي التجارة الخارجية والناتج المحلي الإجمالي.